Long-Term Suppressive cART Is Not Sufficient to Restore Intestinal Permeability and Gut Microbiota Compositional Changes - Ancona, Giuseppe; Merlini, Esther; Tincati, Camilla; Barassi, Alessandra; Calcagno, Andrea; Augello, Matteo; Bono, Valeria; Bai, Francesca; Cannizzo, Elvira S.; d'Arminio Monforte, Antonella; Marchetti, Giulia (Frontiers in Immunology, 2021)
Background We explored the long-term effects of cART on markers of gut damage, microbial translocation and paired gut/blood microbiota composition, with a focus on the role exerted by different drug classes. Methods We enrolled 41 cART naïve HIV-infected subjects, undergoing blood and fecal sampling prior to cART (T0) and after 12 (T12) and 24 (T24) months of therapy. 15 HIV-uninfected individuals were enrolled as controls. We analyzed: (i) T-cell homeostasis (flow cytometry); (ii) microbial translocation (sCD14, EndoCab, 16S rDNA); (iii) intestinal permeability and damage markers (LAC/MAN, I-FABP, fecal calprotectin); (iv) plasma and fecal microbiota composition (alpha- and beta-diversity, relative abundance); (v) functional metagenome predictions (PICRUSt). Results Twelve and 24-month successful cART resulted in a rise in EndoCAb (p=0.0001) and I-FABP (p=0.039) vis-à-vis stable 16S rDNA, sCD14, calprotectin and LAC/MAN, along with reduced immune activation in the periphery. Furthermore, cART did not lead to substantial modifications of microbial composition in both plasma and feces and metabolic metagenome predictions. The stratification according to cART regimens revealed a feeble effect on microbiota composition in patients on NNRTI-based or INSTI-based regimens, but not PI-based regimens. Conclusions We hereby show that 24 months of viro-immunological effective cART, while containing peripheral hyperactivation, exerts only minor effects on the gastrointestinal tract. Persistent alteration of plasma markers indicative of gut structural and functional impairment seemingly parallels enduring fecal dysbiosis, irrespective of drug classes, with no effect on metabolic metagenome predictions.